2016
DOI: 10.1016/j.renene.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Heat recovery from air in underground transport tunnels

Abstract: 5The performance of a typical air source heat pump could be increased dramatically by a relatively stable air 6 temperature with a high humidity, even during the peak heating months. In this short communication we show such 7 conditions exist in the underground transport tunnels of the Glasgow Subway system, where we had conducted an 8 annual survey of air flow, air temperature and relative humidity at thirty different points within the subway network. 9We found relatively stable temperatures and sufficient ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Given the enclosed nature of the platform/tunnel area, a permanent air draft with a year-round mean temperature of 16.7 degrees Celsius and a mean humidity of 68.9% feed the unit. The air flow and pressure at platform level had a mean value of 15.82 m 3 /h and 1.5 Pa respectively [10]. To obtain the maximum output of trains' movements and raise the air input, the condenser unit was positioned at a 30 degree angle to the wall under the stairs (Figure 7).…”
Section: Results and Lessons Learntmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the enclosed nature of the platform/tunnel area, a permanent air draft with a year-round mean temperature of 16.7 degrees Celsius and a mean humidity of 68.9% feed the unit. The air flow and pressure at platform level had a mean value of 15.82 m 3 /h and 1.5 Pa respectively [10]. To obtain the maximum output of trains' movements and raise the air input, the condenser unit was positioned at a 30 degree angle to the wall under the stairs (Figure 7).…”
Section: Results and Lessons Learntmentioning
confidence: 99%
“…The SPT required the condenser not to be visible to the passengers, therefore it was decided to position it below the stairs at the platform level, which is only 10 m below the ground level ( Figure 2). The relatively confined Station platform volume (820 m 3 ) in relation to the recurrent air exchange (15.8 m 3 /h) [10], due to constant train movements and low platform depth, allows for a constant natural air flow at platform level. Based on previous surveys undertaken by the SPT, the air quality at the platform level was similar to the outdoor environment; therefore, no additional air quality monitoring was undertaken.…”
Section: Ashp Installationmentioning
confidence: 99%
See 1 more Smart Citation
“…Railway tunnels represent a reliable waste heat source in cities where public transportation heavily relies on underground metro systems. The potential to recover secondary energy from underground railway tunnels in the UK has been investigated by the authors of [31,32], who analyzed the environment of the subway systems of Glasgow and London, respectively. The authors of [31] highlighted how this opportunity can help in achieving the UK targets for decarbonizing the heating sector through the application of heat pumps, which can reach better performance with warmer and stable source temperatures.…”
Section: Underground Railway Tunnelsmentioning
confidence: 99%
“…The potential to recover secondary energy from underground railway tunnels in the UK has been investigated by the authors of [31,32], who analyzed the environment of the subway systems of Glasgow and London, respectively. The authors of [31] highlighted how this opportunity can help in achieving the UK targets for decarbonizing the heating sector through the application of heat pumps, which can reach better performance with warmer and stable source temperatures. The authors measured the annual temperatures for a station of the Glasgow subway and showed how they range from 15 and 18 • C, while the outside average temperatures can range from 4 to 16 • C, indicating how heat pumps can operate more efficiently using the underground air as a heat source.…”
Section: Underground Railway Tunnelsmentioning
confidence: 99%